2018
DOI: 10.1186/s13048-018-0385-0
|View full text |Cite
|
Sign up to set email alerts
|

Sialylation of EGFR by the ST6Gal-I sialyltransferase promotes EGFR activation and resistance to gefitinib-mediated cell death

Abstract: BackgroundThe ST6Gal-I sialyltransferase is upregulated in numerous cancers, and high expression of this enzyme correlates with poor patient prognosis in various malignancies, including ovarian cancer. Through its sialylation of a select cohort of cell surface receptors, ST6Gal-I modulates cell signaling to promote tumor cell survival. The goal of the present study was to investigate the influence of ST6Gal-I on another important receptor that controls cancer cell behavior, EGFR. Additionally, the effect of ST… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
109
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(118 citation statements)
references
References 51 publications
(46 reference statements)
9
109
0
Order By: Relevance
“…An upstream regulator of DNA repair pathways is EGFR, known to regulate DNA repair, DNA replication and maintenance of genome stability when found in the nucleus (105). A study of ST6GAL1 sialylation in ovarian cancer, suggested that increased ST6GAL1 sialylation confers resistance to chemotherapeutic intervention (106). Of interest, they postulated that this chemoresistance was through direct sialylation of EGFR by ST6GAL1, resulting in heightened activation of EGFR.…”
Section: St6gal1 In the Hallmarks Of Cancermentioning
confidence: 99%
“…An upstream regulator of DNA repair pathways is EGFR, known to regulate DNA repair, DNA replication and maintenance of genome stability when found in the nucleus (105). A study of ST6GAL1 sialylation in ovarian cancer, suggested that increased ST6GAL1 sialylation confers resistance to chemotherapeutic intervention (106). Of interest, they postulated that this chemoresistance was through direct sialylation of EGFR by ST6GAL1, resulting in heightened activation of EGFR.…”
Section: St6gal1 In the Hallmarks Of Cancermentioning
confidence: 99%
“…Several published reports note hypersialylation of cancer cells, including that of the neoplasms of breast (22) cancer. Hypersialylation is associated with, and suggested to be causal to, increased aggressiveness, stemness, resistance to chemotherapeutic agents, ability to survive in stressful conditions like hypoxia and impaired nutrient supply (24,25,27,38). However, when we performed flow cytometry to isolate the two subpopulations showing distinct α2,6 sialic acid levels, the one showing lower levels (which we denoted as medium 2,6-Sial cells) showed greater invasion than high 2,6-Sial cells in both transwell assay and in 3D cultures.…”
Section: Discussionmentioning
confidence: 99%
“…Hypersialylation is one of the most frequently observed changes in glycosylation in many cancer types (22,23). Selective enrichment of terminal α2,6linked sialic acids (referred here-onward as α2,6-Sial), due to overexpression of ST6GAL1, in cancer cell glycocalyces can elicit a wide range of biological outcomes like protection from hypoxia, resistance to chemotherapy, pro-survival and conferral of cancer stem cell phenotype (24)(25)(26)(27).…”
Section: Introductionmentioning
confidence: 99%
“…Sialylation by ST6Gal-1 is thought to maintain a more stem-like state in cancer cells (Schultz et al, 2016) and has been implicated in bladder (Antony et al, 2014), colon (Zhang et al, 2017), breast (Lu et al, 2014), and ovarian cancers (Christie et al, 2008). Multiple works have demonstrated how ST6Gal-1 both confers resistance to chemotherapy (Britain et al, 2018; Schultz et al, 2013) and protects cancer cells from apoptosis by sialylation of Fas (Swindall and Bellis, 2011) and tumor necrosis factor receptor (Holdbrooks et al, 2018). Interestingly, ST6Gal-1 is also the only glycosyltransferase to date in which its soluble form can “extrinsically” glycosylate outside the cell (Manhardt et al, 2017).…”
Section: Critical Glycan Moieties Aberrantly Expressed In Cancermentioning
confidence: 99%